Individual characteristics in arts management careers: investigating the highly sensitive person scale on motivation to lead - Farstad, Christian Winther; Arnulf, Jan Ketil (Frontiers in Psychology, 2024)
Research on personality in leadership indicates that self-selection to leadership careers and artistic careers correlates with diverging personality profiles. People in leadership careers traditionally display lower neuroticism and higher conscientiousness than artistic individuals. In between, there are individuals entering arts management careers. To study these individuals directly, we collected Norwegian data from 91 musical theater students and 102 arts management students and compared with 109 business management students. As expected, conscientiousness and neuroticism predicted artistic careers against business management careers, aligned with the “arts for arts’ sake” myth of artists. Interestingly, arts management careers were not different from artistic careers. They weren’t more motivated to take on leadership roles than performing artists either. However, the Highly Sensitive Person Scale indicated that narrower traits of sensitivity predicted higher levels of motivation to lead in many artists. Some arts and arts management students seem to bring unique talents into forms of leadership particularly useful for artistic organizations. Our findings are discussed in terms of how leadership characteristics operate in the field of art, and the effect of domain-specific characteristics in this setting.